The Value of Serum Elabela in Preeclamptic Women with and without Fetal Growth Restriction at 34 Weeks of Pregnancy: A Case–Control Study - Eham Amer Ali; Amenah Fadhil; Shaymaa Khalid Abdulqader; Wassan Nori; Mustafa Ali Kassim Kassim; Alexandru Cosmin Pantazi (Medical Journal of Babylon)
Background: Reliable screening methods for fetal growth restriction (FGR) are crucial to improve maternal and neonatal outcomes. Preeclampsia (PE) is a specific pregnancy ailment that contributes to FGR. Elabela (Ela), a newly discovered adipokine, was correlated with PE. Objective: As a marker of PE, we aimed to examine Ela’s role in PE women with and without FGR as a possible screening biomarker at 34 weeks of gestation. Materials and Methods: A case–control study started from March 2022 to December 2022 recruited gestational age and body-indexed matched pregnant at 34 weeks into two groups. Healthy controls (55/110) and PE cases (55/110), were further stratified into (15/55) FGR-PE and (40/55) PE-without FGR. Demographics (systolic and diastolic blood pressure and body mass index), biochemical (creatinine, urea, uric acid, urinalysis, alanine transaminase, and aspartate transaminase), hematological (hemoglobin and platelets), and ultrasonic parameters [gestational age, fetal weight, umbilical artery pulsatility index (PI), and amniotic fluid index] were compared for both. Maternal serum Ela was checked by an enzyme-linked immunosorbent assay kit. Results: Serum Ela was significantly low in FGR-PE (10.02 ± 1.63) cases, followed by PE (11.77 ± 1.02) and healthy controls (17.58 ± 2.72), P < 0.001. Ela was significantly inversely correlated with systolic and diastolic blood pressures (r = -0.41, -0.50), respectively; moreover, it was positively and significantly linked to fetal weight and umbilical artery PI (r = 0.42, 0.35), respectively. Conclusion: Strong and significant correlations of serum Ela with FGR markers at high sensitivity 87% and specificity82%, P < 0.001 in PE moms make it a reliable screening for FGR in PE cases. Future studies are warranted for possible therapeutic and prognostic applications in practice.